Administrasi Publik Dalam Perspektif Islam: Kajian Pada Sistem Pemerintahan Umar Bin Khattab - Nanda Herijal Putra (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2021)
This study examines about public administration in an Islamic perspective, studies on the system of government of Umar Bin Khattab. The administrative system was not implemented before Nabi Muhammad SAW moved to Medina, after Nabi Muhammad SAW moved from Mecca to Medina, reading and writing activities began to be carried out among the Muslims and to build a government based on Islamic law. The development of the administration was increasingly rapid during the Caliphate of Umar bin Khattab. This research is a type of library research with a research approach using qualitative research methods. Literature research is research that uses data collection techniques by reviewing books, literature, notes and various reports related to the problem to be studied. Public administration as a discipline that is dynamic in accordance with the times. In line with the times, public administration has changed for the better in accordance with the demands of an increasingly complex era. In the western perspective, public administration has experienced developments starting from the old public administration paradigm, new public management, to the new public service. In an Islamic perspective, administration is known as al-idara. Administration in Islam refers to the Qur'an and its interpretations as well as hadiths and syarahs. The sources of interpretation provide an explanation of the signs of the Qur'an whose position exceeds the general rules relating to the order of people's lives. In the context of public services, excellent service is a must and obligation for both the government and the state civil apparatus. Public services are carried out based on Islamic teachings, namely the services provided must be good, honest, quality and trustworthy.